2012
DOI: 10.1038/ng.2508
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies mutation in CNOT3 and ribosomal genes RPL5 and RPL10 in T-cell acute lymphoblastic leukemia

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is caused by the cooperation of multiple oncogenic lesions1,2. We used exome sequencing on 67 T-ALLs to gain insight into the mutational spectrum in these leukemias. We detected protein-altering mutations in 508 genes, with an average of 8.2 mutations in pediatric and 21.0 mutations in adult T-ALL. Using stringent filtering, we predict seven new oncogenic driver genes in T-ALL. We identify CNOT3 as a tumor suppressor mutated in 7 of 89 (7.9%) adult T-ALLs, and its kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
402
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 378 publications
(425 citation statements)
references
References 54 publications
19
402
3
1
Order By: Relevance
“…Consistent with previous genomic studies (26,38), pediatric ALL leukemia samples in our series showed a low burden of exonic mutations and copy number alterations at diagnosis. Moreover, and with the exception of one T-ALL tumor, which showed a marked increase in mutation load at relapse, the mutation load of these leukemias was only modestly increased at relapse.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Consistent with previous genomic studies (26,38), pediatric ALL leukemia samples in our series showed a low burden of exonic mutations and copy number alterations at diagnosis. Moreover, and with the exception of one T-ALL tumor, which showed a marked increase in mutation load at relapse, the mutation load of these leukemias was only modestly increased at relapse.…”
Section: Discussionsupporting
confidence: 78%
“…S1 and S2 and Datasets S3 and S4). Recurrently somatically mutated genes in our series included known oncogenes and tumor suppressors mutated in B-cell precursor ALL [KRAS, NRAS, Fms related tyrosine kinase 3 (FLT3), Janus kinase 2 (JAK2), Janus kinase 3 (JAK3), and CREBBP] (20) and T-cell ALL [Notch1 (NOTCH1), FBXW7, PHF6, DNM2, WT1, JAK1, JAK3, BCL11B, TP53, CREBBP, RPL10, RUNX1, and CNOT3] (16,(21)(22)(23)(24)(25)(26)(27). In addition, we also identified recurrently ALL mutated genes including ZFHX3, ubiquitin specific peptidase 9, X-linked (USP9X), calcium voltage-gated channel subunit alpha1 H (CACNA1H), EPHA3, SHROOM3, USP7, RPGR, 5-hydroxytryptamine receptor 3A (HTR3A), mediator complex subunit 12 (MED12), teneurin transmembrane protein 3 (TENM3), and IL17RA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This appears to be of importance in human T-acute lymphocyte leukemia (ALL), a childhood tumor more common in males than in females and a corresponding experimental model of the disease [112][113][114] . Additional X-linked players altered in T-ALL are the PHF6 and RPL10 genes, which are mutated almost exclusively in male patients 115,116 . Loss-of-function UTX mutations have also been found in oesophageal SCCs and renal cell carcinomas, which are more frequent in the male population 117,118 .…”
Section: A) X Chromosomementioning
confidence: 99%
“…Over the last decade, studies utilizing microarray analysis of gene expression, DNA copy-number alterations, and next-generation sequencing have provided major insights into the pathogenesis and clinical behavior of ALL. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Most ALL genomes harbor sequence and structural DNA alterations involving coding genes, as well as alterations of noncoding elements such as noncoding RNAs 23 and enhancer elements. 24,25 Here, we consider results from these studies in several categories: (1) identification of new subtypes of ALL that lack recurring gross chromosomal alterations; (2) characterization of the constellations of genetic alterations that define each ALL subtype; (3) the relationship between genetic alterations, clonal heterogeneity, and relapse; (4) identification of inherited genetic variants and mutations linked to ALL susceptibility and outcome; (5) and translating new discoveries to improved diagnostic, prognostic, and precision medicine approaches.…”
Section: Introductionmentioning
confidence: 99%